The Usage of Fly Ash for Reclaimed Asphalt Pavement (RAP), Asphalt Concrete Binder Course (AC-BC) Filler - Ratna Handayani; Ria Asih Aryani Soemitro; Herry Budianto; Januarti Jaya Ekaputri (Institut Teknologi Sepuluh Nopember, 2017)
Material Reclaimed Asphalt Pavement (RAP) and fly ash as waste that whose is abundant. So interesting to be researched. The research will be started by analyze of RAP, be obtained characteristics of aggregates and asphalt, then analyzed on an aggregate gradation; if aggregate gradation does not on gradation envelope will be required the addition of new aggregate. If asphalt does not match the requirements then also be required the addition of new asphalt. The next will be made the composition of mix- design for Asphalt Concrete - Binder Course (AC-BC) with variations addition of fly ash volume as filler. The aim of research to get variations addition of fly ash volume (4%,5% and 6%)